PAPER WASTE MANAGEMENT DI DESA BUMI NABUNG SEBAGAI TUJUAN SDGs DESA “DESA EKONOMI TUMBUH MERATA” - Dalimunthe, Nindytia Puspitasari; Mutiasari Nur Wulan; Sri Hasnawati; Dwi Asri Siti Ambarwati (BEGAWI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract : Purpose: Village SDGs goal number 2: Village economic growth evenly includes: Village SDGs 8: Village economic growth is even; Village SDGs 9: Village infrastructure and innovation according to needs; Village SDGs 10: villages without gaps; and Village SDGs 12: environmentally conscious Village consumption and production will be the focus of this service activity. Environmental problems are still a concern for environmentalists, the government and the wider community. One of the environmental problems is related to waste, namely the large amount of paper waste that has not been utilized. Implementing paper waste management by making recycled paper products that can be used to achieve the SDGs goals, such as for making notes or as a basic material for printing invitation paper, can be a village program to realize these goals. This training activity aims to increase awareness and skills of residents Bumi Nabung District, Central Lampung in processing paper waste into goods that have economic value Methodology/approach: This activity was carried out at Bumi Nabung using lecture and discussion methods. The participants in this activity are teachers so that these skills can be taught to students. Results/findings: Participants were given training in the form of making recycled paper using unused paper by providing counseling through videos on making recycled paper. Participants watched the demo with great enthusiasm. Conclusion: these skills can be applied not only to reduce paper waste but also as a source of income by selling recycled paper.